Unattended automated office blood pressure measurement: Time efficiency and barriers to implementation/utilization. Issue 4 (9th March 2020) - Doane, John; Flynn, Michael; Archibald, Marcus; Ramirez, Dominick; Conroy, Molly B.; Stults, Barry
Abstract: Unattended automated office blood pressure (BP) measurement (u‐AOBP) improves office BP measurement accuracy and reduces white‐coat BP elevation, but there are reservations about its time efficiency in primary care. We used time‐stamp methodology to measure u‐AOBP procedure times performed without a rest period in 130 patients during routine clinic visits to three primary care clinics with 2.5‐4.9 years u‐AOBP experience. We documented the clinical activities of 30 medical assistants during the u‐AOBP procedures. We also assessed MA and clinician satisfaction and knowledge about u‐AOBP performance and interpretation. Median u‐AOBP procedure time was <5 minutes, and MAs engaged in productive clinical activities during 83% of the procedures. Ninety‐three percent of MAs and 100% of clinicians in the clinics agreed that u‐AOBP is an efficient method to improve hypertension management. Barriers to effective u‐AOBP implementation and ongoing utilization included initial difficulty incorporating u‐AOBP into clinic workflow and medical staff knowledge deficiencies concerning correct u‐AOBP performance and interpretation despite prior training and experience with the procedure. Intensive u‐AOBP education and training programs are needed to facilitate effective u‐AOBP implementation into primary care. The time required to perform u‐AOBP can be utilized productively by staff.